Non-tenera Contamination and the Economic Impact of SHELL Genetic Testing in the Malaysian Independent Oil Palm Industry - Ooi, Leslie C.-L.; Low, Eng-Ti L.; Abdullah, Meilina O.; Nookiah, Rajanaidu; Ting, Ngoot C.; Nagappan, Jayanthi; Manaf, Mohamad A. A.; Chan, Kuang-Lim; Halim, Mohd A.; Azizi, Norazah; Omar, Wahid; Murad, Abdul J.; et al. (Frontiers in Plant Science, 2016)
Oil palm (Elaeis guineensis) is the most productive oil bearing crop worldwide. It has three fruit forms, namely dura (thick-shelled), pisifera (shell-less) and tenera (thin-shelled), which are controlled by the SHELL gene. The fruit forms exhibit monogenic co-dominant inheritance, where tenera is a hybrid obtained by crossing maternal dura and paternal pisifera palms. Commercial palm oil production is based on planting thin-shelled tenera palms, which typically yield 30% more oil than dura palms, while pisifera palms are female-sterile and have little to no palm oil yield. It is clear that tenera hybrids produce more oil than either parent due to single gene heterosis. The unintentional planting of dura or pisifera palms reduces overall yield and impacts land utilization that would otherwise be devoted to more productive tenera palms. Here we identify three additional novel mutant alleles of the SHELL gene, which encode a type II MADS-box transcription factor, and determine oil yield via control of shell fruit form phenotype in a manner similar to two previously identified mutant SHELL alleles. Assays encompassing all five mutations account for all dura and pisifera palms analyzed. By assaying for these variants in 10,224 palms or seedlings, we report the first large scale accurate genotype-based determination of the fruit forms in independent oil palm planting sites and in the nurseries that supply them throughout Malaysia. The measured non-tenera contamination rate (10.9% overall on a weighted average basis) underscores the importance of SHELL genetic testing of seedlings prior to planting in production fields. By eliminating non-tenera contamination, comprehensive SHELL genetic testing can improve sustainability by increasing yield on existing planted lands. In addition, economic modelling demonstrates that SHELL gene testing will confer substantial annual economic gains to the oil palm industry, to Malaysian gross national income and to Malaysian government tax receipts.